The Teacher Professional Education Students' Perception on Learning Management System-based Online Learning - Ramdhan, Dadan F; Siregar, Hariman Surya (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research aimed to investigate the perceptions and impacts of online learning utilizing the SPACE (Electronic religious learning system application) among students enrolled in Teacher Professional Education (TPE) programs at State Islamic Religious Colleges. Employing a quantitative approach, the study utilized linear regression analysis and structural equation modeling through AMOS 23. Effectiveness was gauged using indicators proposed by Robert E. Slavin, encompassing quality of learning, appropriateness of learning level, intensity, and time. The study participants comprised students across three Teacher Professional Education Study Programs. The findings revealed that nearly all participants expressed ease in learning and perceived the modules within SPACE as more effective. They also indicated that the materials/modules in SPACE aligned well with the needs of TPE participants and found the learning procedures within SPACE easy to follow. Notably, incentive variables within implementation indicators had a direct influence on perceived ease of use (user convenience), subsequently impacting the perceived usefulness variable. For future research, integrating direct interview data from students and conducting comparative analyses between offline and online implementations in professional education would provide valuable insights.